KAJIAN TEKNIS BUDIDAYA IKAN KAKAP PUTIH (Lates calcarifer) DI BALAI PERIKANAN BUDIDAYA AIR PAYAU (BPBAP) SITUBONDO, KABUPATEN SITUBONDO, JAWA TIMUR - Endang Puji Astuti; Qurrota A'yun; Arida Vitasari; Putri Desi Wulan Sari (Universitas Muhammadiyah Gresik, 2023)
White snapper (Lates calcarifer) is a marine fish that can be referred to as giant sea perch, sea bass, and barramundi. This fish is one of the fishery commodities that have many overseas enthusiasts. The characteristics of fish are that they are easy to cultivate because they grow relatively fast and can adapt well to the environment. However, in the process of cultivation, seeds have low susceptibility to diseases caused by environmental conditions. The solution to overcome this is to improve the quality of the parent and seed. Furthermore, the seeds are cultivated until they reach the consumption size to meet market needs. The purpose of writing this scientific article for street vendors is to find out the cultivation techniques of white snapper at the BPBAP Situbondo Fisheries Center, as well as the problems that occur during cultivation activities. The method used was the active participation method and observation. White snapper cultivationtechniques include broodstock maintenance, hatchery, and rearing, each of which consists of pond preparation, feeding, monitoring water quality, and monitoring pests and diseases. The results of observations obtained from parent-rearing activities were 79% FR, hatchery activities obtained 50% HR and 22% SR, and rearing activities with 0.10% SGR, 4.29 FCR, and 54.43% SR. The obstacle that occurs is the presence of human error in the hatchery unit due to delays in grading, causing low survival rates (SR) that do not meet the requirements. In addition, the rearing unit trash feed is not always available so it does not meet the requirements in the calculation of SR, SGR, and FCR.